Dr. Strangelove [videorecording (DVD)] : or, How I learned to stop worrying and love the bomb - Sellers, Peter, 1925-1980; Scott, George C., 1927-1999; Kubrick, Stanley; Hayden, Sterling, 1916-1986; Bryant, Peter, 1924-1966 (Columbia TriStar Home Entertainment, 2001)
A satire in which the U.S. president and his military advisors struggle ineptly to avert a holocaust after a psychotic Air Force general launches a nuclear attack on the Soviet Union because he fears that the Russians are poisoning the water supply in the United States.